Consequences of groundwater overexploitation on land subsidence in Fars Province of Iran and its mitigation management programme - Golian, Mohsen; Saffarzadeh, Ali; Katibeh, Homayoon; Mahdad, Masoud; Saadat, Habib; Khazaei, Mahdi; Sametzadeh, Ershad; Ahmadi, Aboozar; Sharifi Teshnizi, Ebrahim; Samadi Darafshani, Mahsa; Dashti Barmaki, Majid (Water and environment journal : WEJ, 2021)
Land subsidence induced by rapid groundwater depletion in Fars Province (Iran) has led to serious problems for agricultural lands, structures and infrastructures, also its destructive effects on the Achaemenid Empire monuments has raised national concerns. Over the past three decades, mainly due to the increasing reliance of the economy on agriculture, the number of water wells has grown rapidly (7100 new wells with the annual withdrawal of 1.1 billion m3) and therefore the groundwater storage has decreased 10 billion m3 and groundwater level has declined averagely 11 m. To cease groundwater depletion and land subsidence, Iran's sustainable groundwater management programme that is currently being implemented to sustain aquifers is considered as the main remedy solution. To analyse the efficiency of the programme implementation in sustaining the aquifers of the province so far, the status of aquifers levels before the programme implementation (before 2015) is compared to its current status (after 2015). The results indicate that by implementing the programme, 22 out of 100 aquifers, mostly located in the southern half of the province, have been sustained. Although, mainly due to inappropriate management and limited financial support, 25 aquifers are still in critical condition, some of which are the most important aquifers in the province. However, implementing sustainable groundwater management in basins facing land subsidence due to groundwater overexploitation is important since it can minimize or stop land subsidence by sustaining aquifers and preventing groundwater drawdown.